Salty wives, spirited mothers, and savvy widows capable women of purpose and persistence in Luke's gospel - Spencer, F. Scott (Franklin Scott) (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2012)
Engaging feminist hermeneutics and philosophy in addition to more traditional methods of biblical study, Salty Wives, Spirited Mothers, and Savvy Widows demonstrates and celebrates the remarkable capability and ingenuity of several women in the Gospel of Luke. While recent studies have exposed women's limited opportunities for ministry in Luke, Scott Spencer pulls the pendulum back from a negative feminist-critical pole toward a more constructive center. Granting that Luke sends somewhat "mixed messages" about women's work and status as Jesus' disciples, Spencer analyzes such women as Mary, Elizabeth, Joanna, Martha and Mary, and the infamous yet intriguing wife of Lot -- whom Jesus exhorts his followers to "remember" -- as well as the unrelentingly persistent women characters in Jesus' parables.
Toward bluer skies: reducing the threat level and resurrecting feminist studies of women in Luke -- Can we go on together with suspicious minds? Doubt and trust as both sides of the hermeneutical coin (Luke 15:8-10) -- A woman's right to choose? Mother Mary as spirited agent and actor (Luke 1-2) -- The quest for the historical Joanna: follower of Jesus, friend of Mary Magdalene, and wife of Herod's official (Luke 8:1-3; 24:10) -- A testy hostess and her lazy sister? Martha, Mary, and the household rivals type scene (Luke 10:38-42) -- A hungry widow, spicy queen, and salty wife: "foreign" Biblical models of warning and judgment (Luke 4:25-26; 11:31; 17:32) -- The savvy widow's might: fighting for justice in an unjust world (Luke 18:1-8) -- A capable woman, who can find? We have found some in Luke!
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Women in the Bible; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books